Lactobacillus johnsonii JERA01 activates macrophages and increases Th-1 T cell population in mouse small intestine. - So Yeon Ahn; Hong-Gu Joo; Eun-Ju Ko (PLoS ONE)
Lactobacillus johnsonii is a commensal bacterium isolated from the vaginal and gastrointestinal tracts of vertebrate hosts, including humans. It is a potential anti-inflammatory bacterium. As reported in many animal studies, L. johnsonii supplementation reduces inflammation in the intestine and enhances the epithelial barrier. However, in this study, we observed immunostimulatory effects of heat-killed L. johnsonii JERA01 (LJ) supplementation on antigen-presenting cells, such as dendritic cells and macrophages, in mice. LJ pretreatment increased the expression of maturation markers and TNF-α, IL-6, IL-12p40 production in bone marrow-derived dendritic cells and macrophages (BMDCs and BMDMs). Co-culture of LJ-pretreated BMDCs or BMDMs with lymphocytes enhanced IFN-γ production in vitro. Oral LJ (108 CFU) supplementation induced macrophage infiltration into the peritoneal cavity and Peyer's patch at 12-h after administration, resulting in an increase in the population of IFN-γ-producing T cells in the Peyer's patch. Our investigation revealed the effects of LJ, which activates macrophages and increases the Th-1 T cell population in the intestine, implying the possibility of using L. johnsonii as an immune stimulator.